Quantitative insights into the cyanobacterial cell economy - Zavřel, Tomáš; Faizi, Marjan; Loureiro, Cristina; Poschmann, Gereon; Stühler, Kai; Sinetova, Maria; Zorina, Anna; Steuer, Ralf; Červený, Jan (eLife, 2019)
Phototrophic microorganisms are promising resources for green biotechnology. Compared to heterotrophic microorganisms, however, the cellular economy of phototrophic growth is still insufficiently understood. We provide a quantitative analysis of light-limited, light-saturated, and light-inhibited growth of the cyanobacterium Synechocystis sp. PCC 6803 using a reproducible cultivation setup. We report key physiological parameters, including growth rate, cell size, and photosynthetic activity over a wide range of light intensities. Intracellular proteins were quantified to monitor proteome allocation as a function of growth rate. Among other physiological acclimations, we identify an upregulation of the translational machinery and downregulation of light harvesting components with increasing light intensity and growth rate. The resulting growth laws are discussed in the context of a coarse-grained model of phototrophic growth and available data obtained by a comprehensive literature search. Our insights into quantitative aspects of cyanobacterial acclimations to different growth rates have implications to understand and optimize photosynthetic productivity.
Keywords: phototrophic growth laws; Synechocystis; proteome allocation; systems biology; Cyanobacteria; fotosyntéza; biotechnologie; microbiology; Photosynthesis; proteom; infectious disease; velikost buňky; sinice; světlo; fototrofní procesy; resource allocation; Biotechnology; Phototrophic Processes; growth model; computational biology; photoinhibition; Light; Proteome; light limitation; Cell Size